Assessing a fertilizer program: Short‐ and long‐term approaches. Issue 1 (3rd January 2017) - Clay, David E.; Reicks, Graig; Chang, Jiyul; Kharel, Tulsi; Bruggeman, Stephanie A.H.
Abstract : Increasingly, agronomists are asked to increase yields while simultaneously reducing fertilizer costs and the impact of agriculture on the environment. Achieving these goals is complicated by climatic variability that can reduce fertilizer efficiency and increase yield losses. One technique to improve fertilizer efficiency is to conduct long‐term assessments of the fertilizer program. Specifically discussed here are the importance of field scouting, long‐term N and P assessments, and future opportunities for identifying the yield‐limiting factors. Soil nutrient assessments provide information needed to implement locally adapted fertility programs. Earn 1.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/805 .